Compensated Moment of Electric Vehicle use Electronic Stability Control - Yunanto, Bagus; Siswoyo, Charis Faridchie; Purwanto, Era (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
This research is reporting a skid adjustment method of an electric vehicle passenger car model by using active brake force control to improve vehicle stability in various driving condition. The presence of skid is determined by comparing the tires rotational speed and the free-rolling speed. The discrepancy of the measured velocities between these sensors indicates the presence of skidding. Further, a two wheels front steering model is used in this work. When the model performing a turning motion, the measured yaw rates Obtained from speed sensors and steering angle sensor can also be used and compared to observe the skidding that indicates either understeer or oversteer. Ackerman calculation is used to investigate the motion of the model. Compensated moment method is used for braking system during the test, such as accelerating, braking, turning and straight cruising. The control system for either simulation or operation test was performed using fuzzy logic controller. The results then were compared and analyzed to show the capability of the controller method to improve the performance of the vehicle model.